(untitled) (Bangladesh Veterinarian, 2024)
The Clostridium perfringens causes food poisoning in men and animals. Pasteurized full cream cows’ milk samples (n = 100) were collected from Dhaka North City Corporation (DNCC) in Bangladesh between July 2022 and June 2023. One sample showed the characteristic properties of C. perfringens in Dhanmondi area of DNCC in winter season. Hygienic management should be followed during processing of milk for human consumption. Bang. vet. 2024. Vol. 41, No. 1 – 2, 7 – 12